Promoting ‘discord’ as a platform for learning engagement during COVID-19 pandemic / Mohd Asraf Ayob ... [et al.] - Ayob, Mohd Asraf; Abdul Hadi, Nurulhudaya; Mohd Pahroraji, Mohamad Ezad Hafez; Ismail, Balkhiz; Saaid, Mohammad Nabil Fikri (Universiti Teknologi MARA, 2022)
Many universities shifted to Open Distance Learning (ODL) to ensure the continuity of teaching and learning when Covid-19 struck. One of the applications is ‘Discord’ which has become popular among gamers. Since many university students are gamers themselves, it is vital to investigate the use of Discord in the classroom. Therefore, this paper presents the potential, effectiveness, and satisfaction of using Discord as a digital learning tool among higher education students. Discord is a very convenient way of communication which can be a best platform to engage students and instructors during pandemic. A study was carried out among 81 students through questionnaire survey via Google Form to seek students’ feedback on the usefulness and satisfaction of using Discord as platform for learning interaction and engagement during pandemic. All returned survey was analysed using Statistical Package for Social Science (SPSS) 20 through reliability test, descriptive analysis, and correlation test. The non-parametric statistical methods such as Chi Square and Mann-Whitney U were selected for this study. Both Kolmogorov Smirnov and Shapiro-Wilk Test indicate that the statistically significant result where dependent variable such as the average time spend daily is not normally distributed. The findings from this study shows that Discord is a very convenient application to help with the promotion of learning engagement through its usefulness and user satisfaction. The study shows that the use of Discord may help students in having better understanding by encouraging the active social and learning engagement on Discord platform where students and instructors can have discussion and socialise among members of Discord server in a flexible time and condition.